FAKTOR-FAKTOR PENYEBAB RENDAHNYA KOMPETENSI PEDAGOGIK GURU PAUD KELOMPOK BERMAIN (KB) SE-KECAMATAN RUMBAI KOTA PEKANBARU - Muharni, Muharni; Chairilsyah, Daviq; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract :According to the observations, the authors found that the problem occurs in early childhood teachers play group (KB) in District Rumbai Pekanbaru among many teachers who did not complete the task is not in time, such as making the design of learning activities during the ongoing learning activities, a mismatch between the developmental aspects to be developed with the media, the lack of variation in instructional media, and less varied assessment instruments for students. The purpose of this study was to determine the Factors Contributing to Low Teacher Pedagogic Competence Paud Se-Rumbai District of Pekanbaru. The population in this study were all early childhood teachers play group (KB) in District Rumbai totaling 58 people. However, from the results of observation unknown D2 educated teachers numbered 42 people. In this study, namely saturated sampling wearing a sampling technique used when all members of the population as the sample is numbered 42 teachers. Based on the survey results revealed that early childhood Teacher Pedagogic Competence group play (KB) Se-Tassel District of Pekanbaru classified as moderate. This means that the group of early childhood teachers play (KB) Se-District of Pekanbaru City Tassel good enough to have the ability to plan, implement, and evaluate learning though not maximized. Factors causing low pedagogical competence early childhood teachers play group (KB) Se-Tassel District of Pekanbaru, the educational background factors, education and discipline. The main factors affecting the low dominant pedagogical competence early childhood teachers play group (KB) Se-Tassel District of Pekanbaru is the educational background factors.Key word: teachers perception about principal supervision.